Stability Monitoring and Deformation Laws of the Yuanjue Cave in the Influence Zone of the Unloading Zone. (8th February 2021) - Meng, Zhigang; Wang, Fengnian; Qi, Gan; Cui, Xuebin; Ma, Juan
Abstract : As a representative of cliff-like stone cultural relics, caves are carved on natural mountains and cliffs, which overlap with the influence zone of the geological unloading zone. Cracks in the unloading zone lead to stability issues, including falling blocks, collapse, water seepage, and deformation. This article analyzes the stability of the roof facing the Yuanjue Cave, the cultural heritage site of Dazu Rock Carvings. We systematically analyzed the characteristics of the Yuanjue Cave and established a method to monitor cave stability based on the framework of the protection system. As shown through in-field practice, the monitoring method showed good modularization, construction, and spatial expansion performance in narrow spaces. Taking fracture displacement, roof subsidence, roof denudation rates, and roof pressure as monitoring elements, the method showed high precision over a short timeframe. The deformation law of the surrounding rock mass was also obtained through coupling the analysis of multisource monitoring data in the Yuanjue Cave. The method could integrate protection and monitoring systems, permitting preservation of the Yuanjue Cave and its cultural relics, providing a useful reference for similar cases.